Business and public policy : the role of the Committee for Economic Development: 1942-1967 - Schriftgiesser, Karl; Committee for Economic Development (Englewood Cliffs, NJ : Prentice-Hall, Inc., 1967)
This book recounts the impact of the policies advocated by the Committee for Economic Development, one very prestigious group of businessmen upon the government of the United States. It reveals the near-identity of views on major policy matters over the last twenty-five years between the government on one hand and the "mature corporation" on the other. It includes topics like: the post-war road; taxes and heretics; economic tasks of peace; the Employment Act; stability and flexibility; the first post-war recession; a monetary impasse; Korean interlude; conservatism moves in; looking for tax reform; recession in 1958; defense against inflation; a countercyclical adventure; the great tax cut; beyond the water$1 (Bs edge; tariffs and trade; cooperation for progress; farms, shops and labour; problems of megapolis; managing the government; revitalising federalism; fighting economic illiteracy; and a look at money and credit. s
Includes bibliographical references and index.
lje 18/10/18
Loans
Keywords: Industrial policy; Economic history-United State; United State